Observer Based Adaptive Output Feedback Tracking Control of Robot Manipulators - Zergeroğlu, Erkan; Tatlıcıoğlu, Enver (IEEE, 2010)
In this paper, we propose an observer based adaptive output feedback (OFB) tracking controller for rigid-link robot manipulators. Specifically, we used a model independent observer in conjuction with a desired compensation adaptation law (DCAL) to remove the link velocity dependency of the controller and achieved asymptotic stability of the observer-controller couple despite the uncertainties associated with the system dynamics. Lyapunov based arguments are utilized to illustrate the stability of the proposed controller. Simulation results are included to demonstrate the performance of observer-controller couple.
49th IEEE Conference on Decision and Control (CDC) -- DEC 15-17, 2010 -- Atlanta, GA